MENJUAL SECARA PERSONAL (PERSONAL SELLING) : KIAT EFEKTIF DALAM MENINGKATKAN PENJUALAN HOTEL - Suradnya, I Made (JURNAL KEPARIWISATAAN, 2007)
Due to marketing orientation shift from market share to customer share and customer lifetime value, personal selling plays a more important role as one of the strategies to increase hotel sales and as an effort to maintain long tern relationship with the customers. this paper will discuss the definitions of the role of and practical ways of executing personal selling.